Manajemen Marketing (Pemasaran) Produk Jasa Keuangan Perbankan dalam Perspektif Islam - Nilam Sari (Media Syari'ah, 2012)
This article aims to provide an overview of ethical marketing management for banking products and financial services in accordance with the principles and values of Islam. This paper is divided to several parts, first: to explain what is meant by marketing, scope and importance of marketing in business. The second part: marketing management discusses how ethics in Islam, the third part explains what is the difference between Islamic and conventional view on marketing. Last discussion is about how the ethics and values of Islam applied in marketing management for banking products and services. There are several things to be noted in the discussion of this article, the application of ethical practices in banking companies will always benefit the company both medium and long term. It also can increase the motivation of the crew, to protect the principle of freedom of trade and increase competitive advantages. Overall management strategy that has been created based on ethics will be a success, according to the plan, if the parties have consistently execute marketing strategies implemented, and conduct a review of the marketing strategies that have been implemented if it does not succeed in business.